Internet of Things and Wearable Devices: A Mixed Literature Review - Cano, Carlos Alberto Gómez; Castillo, Verenice Sánchez; Castillo-Gonzalez, William; Vitón-Castillo, Adrián Alejandro; Gonzalez-Argote, Javier (EAI Endorsed Transactions on Internet of Things, 2023)
In recent years, the concept of the Internet of Things (IoT), its different models and emerging conceptual frameworks, have offered new opportunities for the integration of technologies into everyday life. Although initially based on the notion of the link between a physical device, its counterpart in a virtual environment and the technological aspects of that relationship, IoT-based wearable devices now offer multiple contributions to all types of users, from professionals and organizations to ordinary people. However, there are inaccuracies, abundant definitions, limited clarity in terms of trends, benefits, components, challenges and future lines of research. In this sense, a mixed literature review study was conducted. The mixed design, of dominant type (CUAN-qual), was composed of a quantitative analysis of bibliometric type and a qualitative analysis of thematic type and embedded in the first one. Data are provided on the main trends observed in the bibliometric indicators studied, a synthesis of some qualitative indicators of particular relevance and pertinence. In addition, future lines of research are presented to address strengths and challenges in this field.
Keywords: Internet of Things; wearable devices; bibliometrics